A new cost-effective method to evaluate collagenase activity using nano-graphene oxide - Ahmad Gholami; Narjeskhatoon Abootalebi; Maryam Nazem; Elahe Hosseini Shirkosh; Younes Ghasemi (Shiraz University of Medical Sciences, 2017)
Graphene oxide (nGO) is considred as a good nano carrier for enzymes to protect them in biological media against proteolytic activity and extend their activity and stability. In this paper, we reported a new inexpensive collagenase assay using graphene oxide nanosheets (nGO) for Coomassie brilliant blue (CBB) staining. Collagenase enzymes was attached to nGO and added to microwells containing dried collagen that covered bottom of wells. The optical absorption (590nm) was linearly increased parallel to increasing the concentration of collagen. The concentraton of collagenase enzyme can be measured by this assay after staining with CBB after overnight incubation with collagen. This technique is a simple, safe, inexpensive and relatively fast method for evaluation of collagenase enzyme and could be applicable for pharmaceutical and industrial purposes.